Negative pion photoproduction on a deuteron by quasi-real photons at large proton momenta; Nucleus 2015. New Horizons in Nuclear Physics, Nuclear Engineering, Femto- and Nanotechnologies - Dmitriev V. F. Vladimir Fedorovich; Dusaev R. R. Renat Ramilyevich; Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Loginov A. Yu. Aleksey Yurievich; Nikolenko D. M. Dmitry Mitrofanovich; Rachek I. A. Igor Anatoljevich; Stibunov V. N. Victor Nikolaevich; Shestakov Yu. V. Yury Vadimovich; Toporkov D. K. Dmitry Konstantinovich; Zevakov S. A. Sergey Aleksandrovich (2015, 2015)
Title screen